Structure and effective interactions in model colloidal suspensions: a molecular dynamics simulation study. (2nd September 2020) - Padidela, Uday Kumar; Behera, Raghu Nath
ABSTRACT: Structure and properties of model colloidal suspensions in bulk solutions have been investigated using classical molecular dynamics simulations. The system consists of spherical particles (macroscopic colloids and microscopic counterions and/or coions) in a continuum solvent and is described using the primitive model. Variations in different properties with system parameters (colloid size, charge, concentration etc.) have been investigated. An effective one-component model [Adelman SA. J. Chem. Phys. 1976;64:724–731] of the multicomponent suspension is used to calculate the effective colloid–colloid potential, which develops an attractive minimum with increase in charge, size and concentration of colloid.